COMMUNICATION DISASTER HANDLING IN MOUNT SINABUNG ERUPTIONS - Fatmawardy Lubis; Yovita Sabarina Sitepu; Munzaimah Masril (Jurnal Ilmiah Ilmu Komunikasi Communique, 2021)
This article presents the communication disaster treatment received by the refugees of Mount Sinabung Eruptions in Karo Regency. The main problem here is that the government very focused on physical development that communcation matters for the refugees. Communication disaster treatment is very effective to reduce the risk in disaster. This treatment supposed to held in every phase of disaster, mitigation, preparedness, respond, and recovery. Most of the time, the government did not pay attention about communication process at all especially at the mitigation and preparednes phases. There was some communication treatment at the respond and recovery phases, but it is not maximal. Even in recovery phase, the action is having an unfinish solution. They build the building, the gave land to the refugees, they gave food, but they did not gave enough information about the important situations.